Importance of initial management and surgical treatment after hydrofluoric acid burn of the finger. Issue 1 (February 2017) - Han, Hyun Ho; Kwon, Byung Yeun; Jung, Sung No; Moon, Suk-Ho
Highlights: No guidelines are available for the hydrofluoric acid-burned digit. Initial management is of great importance to minimize tissue damage. The physician should wait at least 7 days so the degree of damage can be classified. Durable reconstruction techniques should be employed in cases of deep layer injuries. Abstract: Occupational injuries to digits due to hydrofluoric acid (HFA) are frequently encountered. They have distinctive features, including intense pain, progressive tissue necrosis, and possible bone erosion. To minimize tissue damage, it is of great importance to execute prudent preoperative assessment and determine the correct surgical modality to reconstruct and maintain the function of the hand. However, proper protocols for fingers have not been presented in previous studies. Eight cases with HFA burn to digits were presented to the emergency room. Wounds were immediately irrigated with saline, calcium gluconate was applied topically to block destructive effects of fluoride ions. Blisters that could lead to progressive tissue destruction were debrided. A fish-mouth fasciotomy was performed and prostaglandin was administered intravenously to maintain maximal distal circulation. Wounds were evaluated daily for apparent demarcation for 6 or 7 days. Digits were reconstructed with free sensate second toe pulp-free flap to provide sufficient padding for the fingertip. All patients showed excellent recovery with stable flaps with acceptable external contour, durable soft tissue padding, and full range of motion of affected joints. In conclusion, when a patient is admitted due to HFA exposure to the finger, early treatment including irrigation, topical neutralizers, and fasciotomy are of great importance to minimize tissue damage. In addition, a physician should wait at least 7 days until the degree of damage to the tissue can be classified so that the physician can decide whether aggressive debridement should be proceeded. In case of deep layer injuries of weight bearing portions such as finger pulp, reconstruction techniques utilizing durable tissues such as partial second toe pulp free flap should be employed.